ISLAM DI TENGAH KONFLIK DALAM DINAMIKA PERKEMBANGAN IPTEK DAN KEBUDAYAAN - Mulkhan, Abdul Munir (Jurnal Bestari, 2001)
Olobilly, an Islanuc modernization succeeded to liberate the moslem countries from colonialism, but defeated to improve the social, science, and technology pouch of an Islamic thought. The development of an ideological basis within the absence of an intellectual costume caused these countries trapped in a secular traditions of social, science and technology. Islam was, the writer said, snared between two high culture that had been not dependent on the dichotomy yet. Besides, this article talked the modem social, science and technology theory presumably failed to establish the human civilization. What do the moslem intellectual elite and Islamic universities must do? This following discussion will focus on it.